An Unusual Presentation of Thyroid Gland Carcinoma: A Case Report - Shrestha, Kundan Kumar; Jha, Anil Kumar; Joshi, Rupesh Raj; Rijal, Anupama Shah; Dhungana, Anup; Regmi, S; Amatya, A (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10158 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 17-18